Protein expression patterns of the yeast mating response. Issue 6 (13th May 2016) - Yuan, Haiyu; Zhang, Rongfei; Shao, Bin; Wang, Xuan; Ouyang, Qi; Hao, Nan; Luo, Chunxiong
Abstract : We systematically studied dynamic protein expression patterns of the mating pathway under two conditions with high temporal resolution. Abstract : Microfluidics, in combination with time-lapse microscopy, is a transformative technology that significantly enhances our ability to monitor and probe biological processes in living cells. However, high-throughput microfluidic devices mostly require sophisticated preparatory and setup work and are thus hard to adopt by non-experts. In this work, we designed an easy-to-use microfluidic chip, which enables tracking of 48 GFP-tagged yeast strains, with each strain under two different stimulus conditions, in a single experiment. We used this technology to investigate the dynamic pattern of protein expression during the yeast mating differentiation response. High doses of pheromone induce cell cycle arrest and the shmoo morphology, whereas low doses of pheromone lead to elongation and chemotrophic growth. By systematically analyzing the protein dynamics of 156 pheromone-regulated genes, we identified groups of genes that are preferentially induced in response to low-dose pheromone (elongation during growth) or high-dose pheromone (shmoo formation and cell cycle arrest). The protein dynamics of these genes may provide insights into the mechanisms underlying the differentiation switch induced by different doses of pheromone.